International macroeconomic dynamics - Turnovsky Stephen J (Cambridge MIT Press, 1997)
International Macroeconomic Dynamics provides extensive applications of important macroeconomic dynamic models to the international economy. It adopts the main contemporary macroeconomic framework, the representative agent model, and develops a series of
Keywords: Econometric models; International economic relations; International finance; Macroeconomics